The literary Kierkegaard - Ziolkowski, Eric Jozef (Northwestern University Press, 2011)
From Clouds to Corsair: Kierkegaard, Aristophanes, and Socrates -- The pure fool and the knight of faith: Wolfram's Parzival and the stages of existence -- From romantic aesthete to Christian analogue: Don Quixote's sallies in Kierkegaard's authorship -- Saying not quite "everything just as it is": Shakespeare on life's way -- "Sorrow's changeling": irony, humor, and laughter in Kierkegaard and Carlyle